2006
DOI: 10.1007/s10640-006-9044-9
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of the Environmental Kuznets Curve: Turning Point and Public Policy

Abstract: We set up a simple dynamic macroeconomic model with (i) polluting consumption and a preference for a clean environment, (ii) increasing returns in abatement giving rise to an EKC and (iii) sustained growth resulting from a linear final-output technology. There are two sorts of market failures caused by external effects associated with consumption and environmental effort. The model is employed to investigate the determinants of the turning point and the cost effectiveness of different public policies aimed at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(41 citation statements)
references
References 21 publications
0
39
0
2
Order By: Relevance
“…Finally, there was a lack of market instruments, and economic markets themselves inhibited the ability to address environmental issues [31,36,40,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Fieldman [76] compared liberal market economies in the UK and USA with coordinated market economies in Germany and Japan in terms of their influence over pollution.…”
Section: Interrelated Structural Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, there was a lack of market instruments, and economic markets themselves inhibited the ability to address environmental issues [31,36,40,57,[59][60][61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76]. Fieldman [76] compared liberal market economies in the UK and USA with coordinated market economies in Germany and Japan in terms of their influence over pollution.…”
Section: Interrelated Structural Causesmentioning
confidence: 99%
“…The majority of these studies cited insufficient incentives to adopt environmentally sustainable practices as a trap and argued for greater economic incentives [30,32,38,42,45,55,63,66,67,69,74,75,83,84,95,102,117]. Some found that there were insufficient incentives to implement a policy or comply with regulations as a result of either a lack of official accountability or a lack of public demand for action [34,36,48,54,60,82,87,108,109].…”
Section: Implementation Trapsmentioning
confidence: 99%
“…The causal complexity of this analysis can be exemplified along the lines of the previously examined determinants of transition: Due to their manifold interactions, the respective contributions of (a) to (d) to the development of the income-pollution relation are hard to delineate -empirically as well as theoretically. As a consequence, papers that concentrate on the theoretical underpinnings of the income-pollution relation have mostly dealt with potential drivers in a one-by-one fashion (see, for example, Smulders et al, 2005;Egli and Steger, 2007).…”
Section: From Theory To Evidencementioning
confidence: 99%
“…The papers by Egli and Steger (2006) and Soretz (2006) study the incentives to invest in clean technologies, in particular in the presence of increasing returns to abatement activities and uncertainty, respectively. The paper by Cunha-e-Sa´and Reis (2006) analyses a discrete jump in technology towards cleaner production.…”
Section: Lucas Bretschger and Sjak Smuldersmentioning
confidence: 99%